PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES DAN TIPE NUMBER HEAD TOGETHER TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI KELAS X ILMU-ILMU SOSIAL SMA NEGERI 4 TAKALAR - Rahman, Nawir; Hasyim, Ahmad; Jalil, Muh. (STKIP Pembangunan Indonesia Makassar, 2019)
The purpose of this study are: 1). To find out student learning outcomes in economic subjects class X Social Sciences 4 SMA Negeri Takalar through the application of cooperative learning models examples non examples. To find out student learning outcomes in economic subjects class X Science Social Sciences of SMA Negeri 4 Takalar through cooperative application type number head together? 2). To find out the differences in student learning outcomes in economic subjects class X Social Sciences 4 SMA Negeri Takalar between the application of cooperative learning model types examples non examples with type head together. This type of research is quantitative. This study was carried out on a population of 105 people, with a sample of 26 people, the results showed that: 1) student learning outcomes were higher on the implementation of cooperative learning model number head together type compared to cooperative learning models examples non examples. 2) Students are more active in learning on the application of cooperative learning model type number head together compared to cooperative learning models of examples non examples. 3) The research hypothesis which reads